Enhancing Engineering Education Through Reflective Practice in a Public University in Nigeria - Salau, Daniel; Osho, Esther; Adewumi, Olayinka Omowunmi; Olayemi, Moses (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This work-in-progress paper presents emerging empirical findings of an ongoing comparative research effort that hypothesizes that Reflective Practice (RP) enables engineering educators to better serve students in the Nigerian higher education context. It considers RP as a pedagogical intervention and presents the results of an evaluation of its impact on student learning at a public university in Nigeria. Seventy-six (76) undergraduate engineering students participated in the study. The research questions (RQ) guiding this study were: What is the impact of RP on students’ learning experiences (RQ1), and how do these experiences compare with the control courses that did not employ RP (RQ2)? Utilizing Kolb's reflective cycle as the theoretical framework, a causal-longitudinal approach was adopted to design two pre- and post-intervention surveys on Qualtrics, each comprising items that explored student engagement, perceptions of instructional design, and impacts on learning outcomes. The instructors’ reflections and pedagogical interventions were tracked using Penzu, an online diary. Preliminary findings, comparing RQ1 and RQ2 with the control and treatment courses, suggest that students had better learning experiences. This study argues that RP enhances educators’ teaching styles and positively influences students’ learning experiences and the result using the Wilcoxon Signed-Rank Test showed a statistically significant difference in student experience (p < 0.05) but no significant difference in student engagement (p > 0.05), suggesting that the intervention had a positive impact on student experience but not on engagement.